PENGEMBANGAN MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION (PBI) PADA MATERI PENCEMARAN LINGKUNGAN UNTUK MENINGKATKAN TINDAKAN PEDULI TERHADAP LINGKUNGAN DI MADRASAH ALIYAH NEGERI DARUSSALAM KABUPATEN ACEH BESAR - Ruslaini ,; Djufri ,; Hafnati Rahmatan (Universitas Islam Negeri Ar-Raniry, 2015)
Care is one of the results of the attention of an event or a learning process that occurs naturally. Concern for the environment is expressed in the form of verbal action. This study aims to improve the action of caring for the environment through the implementation of problem based learning model on the material of environmental pollution . This study was a descriptive study. The instrument used in this study was enclosed questionnaire with Likert scale that consisted of 20 questions, including 13 positive questions and 7 negative questions to improve the concerned action to the environment.The results of action caringconcerned about the environment, it was found thatthere was 70% of positive statement with strongly agree category, 68% of negative statement catagorized as strongly disagree. Thus, it can be concluded that the development of PBI model on the topic of environmental pollution could improve the action concerned to the environment.